Nickel-mediated reductive coupling of neopentyl bromides with activated alkenes at room temperature and its synthetic application. Issue 33 (16th August 2019) - Ouyang, Yan; Peng, Yu; Li, Wei-Dong Z.
Abstract: Reductive coupling of sterically hindered neo pentyl bromides with activated alkenes mediated by the in situ generated Ni(0) complexes along with some feedstock is achieved in good yield under the mild conditions. This practically useful method of C( sp 3 )−C( sp 3 ) bond formation provides a complementary approach to the traditional conjugate addition of preformed organometallic reagents to electrophilic olefins, which often requires cryogenic temperature and rigorous exclusion of air and moisture. The robust application of this reductive coupling reaction was demonstrated in a formal synthesis of stereodivergent (−)-copacamphor and (−)-ylangocamphor, which are valuable intermediates for a class of tricyclo[5.3.0.0 3, 8 ]decane sesquiterpenes. Moreover, this convenient protocol resulted in a facile access to the homolog of Corey aldehyde en route to prostaglandins, implying the possible involvement of radical-like species. Graphical abstract: Image 1